2018
DOI: 10.1111/echo.14221
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass regression after aortic valve replacement: Sex differences or effect of different methods of indexation?

Abstract: Background:The influence of sex on regression of left ventricular (LV) hypertrophy (LVH) after aortic valve replacement (AVR) for aortic stenosis (AS) remains elusive.The lack of consensus on how to correct LV mass (LVM) for body size, and different normalcy values, contribute to inconclusive results. Methods:In 164 consecutive patients (mean age 80 ± 4 years, 59% females) with AS, we analyzed LVM (Devereux formula) before and 1 year after AVR (St.Jude Trifecta bio-prosthesis). LVM was indexed to BSA (Du Bois … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Early M-mode and two-dimensional transthoracic echocardiography data suggested that women developed greater LV wall thickness given a similar severity of AS 14 15. However, in a recent study, women and men had similar LV mass (LVM) and prevalence of LV hypertrophy for similar AS severity, regardless whether LVM was indexed for BSA or height 1.7 16. However, with cardiac MRI (CMRI), women often exhibited lower LVM with a smaller LV cavity size, whereas men developed a larger LV cavity and greater LV wall thickness and mass for similar AS severity and comorbidities 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…Early M-mode and two-dimensional transthoracic echocardiography data suggested that women developed greater LV wall thickness given a similar severity of AS 14 15. However, in a recent study, women and men had similar LV mass (LVM) and prevalence of LV hypertrophy for similar AS severity, regardless whether LVM was indexed for BSA or height 1.7 16. However, with cardiac MRI (CMRI), women often exhibited lower LVM with a smaller LV cavity size, whereas men developed a larger LV cavity and greater LV wall thickness and mass for similar AS severity and comorbidities 17 18.…”
Section: Introductionmentioning
confidence: 99%